2005
DOI: 10.1094/pd-89-0712
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Biological Control Agents and Systemic Acquired Resistance Inducers Against Bacterial Spot on Tomato

Abstract: Two strains of plant growth-promoting rhizobacteria, two systemic acquired resistance inducers (harpin and acibenzolar-S-methyl), host-specific unformulated bacteriophages, and two antagonistic bacteria were evaluated for control of tomato bacterial spot incited by Xanthomonas campestris pv. vesicatoria in greenhouse experiments. Untreated plants and plants treated with copper hydroxide were used as controls. The plant growth-promoting rhizobacteria or a tap water control were applied as a drench to the pottin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
1
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 15 publications
2
90
1
5
Order By: Relevance
“…They have been used as part of integrated disease management because of ease of application, can be used in combination with other bactericides or as an alternative to other bactericides, and have a relatively low cost (27). Moreover, because phages are generally quite specific for their host bacterial species, they can be specially targeted towards the pathogen without affecting other members of the bacterial community (16).…”
mentioning
confidence: 99%
“…They have been used as part of integrated disease management because of ease of application, can be used in combination with other bactericides or as an alternative to other bactericides, and have a relatively low cost (27). Moreover, because phages are generally quite specific for their host bacterial species, they can be specially targeted towards the pathogen without affecting other members of the bacterial community (16).…”
mentioning
confidence: 99%
“…When tomatoes are grown on ultraviolet reflective mulches, Momol et al (2004) concluded that acibenzolar-S-methyl provided little additional disease protection because of the large effect of the mulch. Nevertheless, acibenzolar-S-methyl is highly effective against bacterial pathogens that afflict tomatoes (Obradovic et al, 2005;Pradhanang et al, 2005), making it an excellent replacement for copper and mancozeb sprays on ultraviolet reflective mulches as well as standard black plastic mulch.…”
Section: Systemic Acquired Resistancementioning
confidence: 99%
“…The latter problem is an especially difficult challenge given that phages can be inactivated by heat, pH extremes, desiccation, UVA and UVB irradiation, exposure to certain chemical pesticides such as copper compounds, or washed off from surfaces by rain [41,82,86]. Consequently, the harsh phyllosphere environment is not ideal for phage survival and therefore results in the loss of phage viability unless they are protected during treatments [41,43,58,[86][87][88]. The lack of standardization of phage preparations and the lack of criteria for purity and efficacy makes it extremely difficult to compare most of the studies that had been published.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Implementing this kind of phage application twice a week, early in the morning prior to sunrise, provided a significantly more effective form of disease control of tomato bacterial spot than the standard copper-mancozeb treatment [42]. Strategies to improve phage persistence in the hostile plant leaf surface environment include protective carrier formulations [86][87][88] consisting mainly of milk, sugar, and flour [41], adequate phage concentration, proper frequency and timing of application relative to the appearance of the bacterial pathogen [23,43], and the avoidance of sunlight. A further pivotal strategy to improve phage persistence is the establishment of a non-pathogenic bacterial host population in the phyllosphere for maintaining phage populations, as well as potentially serving as biocontrol agents due to the antagonistic effects these bacterial strains usually have [39].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%